Management of Nitrogen and Calcium in Pear Trees for Enhancement of Fruit Resistance to Postharvest Decay - Sugar, David (1992)
Management of pear (Pyrus communis L.) trees for low N and high Ca content in the fruit reduced the severity of postharvest fungal decay. Application of N fertilizer 3 weeks before harvest supplied N for tree reserves and for flowers the following spring without increasing fruit N. Calcium chloride sprays during the growing season increased fruit Ca content. Nitrogen and Ca management appear to be additive factors in decay reduction. Fruit density and position in the tree canopy influenced their response to N fertilization. Nitrogen: Ca ratios were lower in fruit from the east quadrant and bottom third of trees and from the distal portion of branches. High fruit density was associated with low N: Ca ratios. Nutritional manipulations appear to be compatible with other methods of postharvest decay control.